2017
DOI: 10.3847/1538-3881/aa7b80
|View full text |Cite
|
Sign up to set email alerts
|

The Star Blended with the MOA-2008-BLG-310 Source Is Not the Exoplanet Host Star

Abstract: High resolution Hubble Space Telescope (HST) image analysis of the MOA-2008-BLG-310 microlens system indicates that the excess flux at the location of the source found in the discovery paper cannot primarily be due to the lens star because it does not match the lens-source relative proper motion, µ rel , predicted by the microlens models. This excess flux is most likely to be due to an unrelated star that happens to be located in close proximity to the source star. Two epochs of HST observations indicate prope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 69 publications
2
48
0
Order By: Relevance
“…Another, more definitive, approach is to observe this event in the future when we can expect to detect the lens-source separation through precise PSF modeling with high-resolution space-based data (Bennett et al 2007 or direct resolution with AO imaging (Batista et al 2015). The lens-source relative proper motion value of m = -+ -4.88 mas yr rel 0.17 0.14 1 indicates that we can expect to be able to resolve the lens, if it provides a large fraction of the excess flux in ∼2022 using HST (Bhattacharya et al 2017) and in 2026 using Keck AO (Batista et al 2015). In Section 5.2, we obtained the observed extinction value A I, obs =0.98±0.07, and color excess values of E(V − I) obs = 0.82±0.04, E(V − H) obs =1.67±0.11, and E(I − H) obs = 0.81±0.07.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another, more definitive, approach is to observe this event in the future when we can expect to detect the lens-source separation through precise PSF modeling with high-resolution space-based data (Bennett et al 2007 or direct resolution with AO imaging (Batista et al 2015). The lens-source relative proper motion value of m = -+ -4.88 mas yr rel 0.17 0.14 1 indicates that we can expect to be able to resolve the lens, if it provides a large fraction of the excess flux in ∼2022 using HST (Bhattacharya et al 2017) and in 2026 using Keck AO (Batista et al 2015). In Section 5.2, we obtained the observed extinction value A I, obs =0.98±0.07, and color excess values of E(V − I) obs = 0.82±0.04, E(V − H) obs =1.67±0.11, and E(I − H) obs = 0.81±0.07.…”
Section: Discussionmentioning
confidence: 99%
“…However, Bhattacharya et al (2017) use HST imaging to show that the excess flux at the position of the MOA-2008-BLG-310 source is not due to the lens star, and N. Koshimoto et al (2017, in preparation) have developed a Bayesian method to study the possibility of excess flux from stars other than the lens star. Possibilities include unrelated stars and companions to the source and lens stars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also significant work needed on microlensing simulations to better understand the information that WFIRST will be able to measure for each planet it finds. This is especially the case for host mass measurements, which will be possible though one or more of the techniques: detecting the host as it separates from the source and measuring image elongation, color-dependent centroid shifts or directly resolving the lens (e.g., Bennett et al 2007;Henderson 2015;Bhattacharya et al 2017), measuring the microlensing parallax with or without finite source measurements (e.g., Yee et al 2013;Yee 2015;Bachelet et al 2018), or even measuring astrometric microlensing (Gould & Yee 2014). The error budget of these measurements is likely to be dominated by systematic errors, and so more detailed end-to-end simulations of the stacking, photometry and astrometry pipelines are likely necessary in order to fully understand WFIRST's capabilities.…”
Section: Future Improvementsmentioning
confidence: 99%
“…In addition to this event, there are a number of planetary microlensing events that have had excess starlight detected at the position of the source in the high angular resolution followup observations, however very few managed to measure the lens-source separation. Under the assumption that this excess flux is due to the planetary host star, a number of papers have claimed to determine the host star mass (Janczak et al 2010;Kubas et al 2012;Batista et al 2014), but further follow-up observations by Bhattacharya et al (2017) have indicated that the excess flux for one of these events was not due to the host star. A detailed analysis by Koshimoto et al (2017b) showed that excess star light that is unresolved from the source can often be due to stars other than the lens, such as companions to the source or lens, or unrelated stars.…”
Section: Introductionmentioning
confidence: 99%